2017
DOI: 10.1038/ejhg.2016.198
|View full text |Cite|
|
Sign up to set email alerts
|

Reconstructing the population history of the largest tribe of India: the Dravidian speaking Gond

Abstract: The Gond comprise the largest tribal group of India with a population exceeding 12 million. Linguistically, the Gond belong to the Gondi-Manda subgroup of the South Central branch of the Dravidian language family. Ethnographers, anthropologists and linguists entertain mutually incompatible hypotheses on their origin. Genetic studies of these people have thus far suffered from the low resolution of the genetic data or the limited number of samples. Therefore, to gain a more comprehensive view on ancient ancestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
10
1
Order By: Relevance
“…Since language shift has previously been reported amongst Central Indian tribes 10,32 , we presume that this is also the case with the Kols sampled in the present study. However, we note that a similar model did not appear to apply to the Gond in our previous studies 7,20 . Therefore, in this study we used large number of autosomal and mitochondrial DNA markers to investigate the conflicting association of Kols as well as their inter and intra population affinities ( Supplementary Tables 1 and 2).…”
Section: Methodscontrasting
confidence: 55%
See 2 more Smart Citations
“…Since language shift has previously been reported amongst Central Indian tribes 10,32 , we presume that this is also the case with the Kols sampled in the present study. However, we note that a similar model did not appear to apply to the Gond in our previous studies 7,20 . Therefore, in this study we used large number of autosomal and mitochondrial DNA markers to investigate the conflicting association of Kols as well as their inter and intra population affinities ( Supplementary Tables 1 and 2).…”
Section: Methodscontrasting
confidence: 55%
“…Caste and tribal affinities in South Asia are factors known to have played a vital role in shaping the genetic landscape of the subcontinent 4,18,19 . In our attempt to understand this genetic complexity, we have assessed the ancestry and geneflow pattern of the major tribal populations of South Asia 7,20,21 . In present study we evaluated the genetic affinities of the Kol population, which, as the third largest tribal population of South Asia, comprises ~1.7 million people (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Roughly one quarter of the ancestral components in the Mundas’ genome (k6 – k12) are shared with Southeast Asians. There are two populations with a similar genetic profile to the Mundas in Central India: Dravidian speaking Gond who are known to have received a substantial gene flow from the Munda speakers 18 and a linguistic isolate Nihali.…”
Section: Resultsmentioning
confidence: 99%
“…For a more detailed view of the temporary aspects of admixture, we assessed the sharing of DNA segments that are identical by decent between Munda speakers and other populations. Refined IBD analysis 20 showed that from India, Mundas share the highest number of DNA segments identical by descent (IBD) with Dravidian speaking Chenchus (1.68; CI: 1.46 – 1.91) and Indo-European speaking Chamar (1.63; CI: 1.26 – 2.11) when disregarding Nihali and Gond tribes as Nihali, a language isolate, are possibly related to Munda and the Gond are reported to have received gene flow from the Mundas 18 . From Southeast Asia the sharing is highest with Mah Meri (2.04; CI: 1.79 – 2.33) and Temuan (1.93; CI: 1.67 – 2.24) tribes from Peninsular Malaysia, followed by Jakun and Che Wong from the same area (Figure 2, Supplementary Table S3).…”
Section: Resultsmentioning
confidence: 99%